Regenerability of fly‐ash derived zeolite NaP1: Evaluation via copper recovery. Issue 4 (9th November 2022) - Ankrah, Archibald Frank; Tokay, Begum; Snape, Colin E.
Abstract: Effective regeneration of adsorbents is considered as one of the essential qualities for commercial use. However, most of the studies have only reported the adsorption properties and overlooked the reuse of adsorbents. In this study, we determined the regenerability and reusability of fly‐ash derived zeolite (FADZ) NaP1. These adsorbents have become popular to remove pollutants from water, including toxic metals, since they are less expensive, compared to their counterparts, and can be synthesized from a waste product. We evaluated the efficiency of copper (Cu 2+ ) ions recovery from water using multiple regeneration solutions due to medium adsorption selectivity towards Cu 2+ . We determined the time required for the regeneration using acid, base, and salt solutions. The suitable pH and solution while maintaining the structure of the zeolite were studied. Up to 90% recovery was achieved via three successive regenerations, each taking 3 h using 3 M KCl and 3 M NaCl solutions. X‐ray diffraction (XRD) and fluorescence showed changes in structure after regeneration at pH < 5 and contact time <6 h. The desorption kinetics using KCl solutions can be described by pseudo‐second order model. Freundlich model represents the desorption of Cu 2+ ions better than the Langmuir model due to regression coefficient (R 2 ) values in the range of 0.998–1.0. Results suggest a strong ion exchange mechanism as the main driving force for desorption. The type of anions (such as Cl − and OH − ) in solution influences regeneration in addition to the exchanging cation. Abstract : In this study, we evaluated regenerability and reusability of fly‐ash derived NaP1 zeolite using copper (II) ions from water. We determined the time required for the regeneration using acid, base, and salt solutions. The suitable pH and solution while maintaining the structure of the zeolite were studied. Up to 90% recovery was achieved via three successive regenerations, each taking 3 h using KCl and NaCl solutions.